2015
DOI: 10.1111/hex.12328
|View full text |Cite
|
Sign up to set email alerts
|

‘Do I need to become someone else?’ A qualitative exploratory study into the experiences and needs of adults with ADHD

Abstract: Background Attention deficit/hyperactivity disorder (ADHD) is a common psychiatric disorder in childhood which has recently been acknowledged to persist into adulthood in two-thirds of cases. However, the problems faced by adults with ADHD in their daily lives remain largely unexplored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…It was revealed that the participants who chose social withdrawal simply to avoid social rejection suffered loneliness as a consequence. Similarly, feelings of social rejection was found in the previous mentioned study by Schrevel et al (2016). That adults with ADHD suffer from loneliness was also identified in a study by Stickley, Koyanagi, Takahashi, Ruchkin, and Kamio (2017).…”
Section: According Tosupporting
confidence: 73%
See 2 more Smart Citations
“…It was revealed that the participants who chose social withdrawal simply to avoid social rejection suffered loneliness as a consequence. Similarly, feelings of social rejection was found in the previous mentioned study by Schrevel et al (2016). That adults with ADHD suffer from loneliness was also identified in a study by Stickley, Koyanagi, Takahashi, Ruchkin, and Kamio (2017).…”
Section: According Tosupporting
confidence: 73%
“…The participants desire to be accepted is expressed, however they could feel that their desire seldom was was fulfilled. Lack of acceptance and understanding by their social environment was also found in the study by Schrevel et al (2016), which focused on the problems and needs of adults with ADHD (N ¼ 52, aged 21 and older, mean age 43 years). This kind of social misunderstanding resulted in feelings of not being good enough, feelings that likely remain when getting older.…”
Section: According Tomentioning
confidence: 68%
See 1 more Smart Citation
“…The previous research findings on ADHD have shown motor coordination issues to persist into adulthood [46]. The absence of motor coordination may be related to greater emphasis adults with ADHD and their environment place on social/ relationship problems and subsequent effect on self-image and self-esteem than on the physical issues being present [47,48]. Another explanation may be that motor coordination issues generally receive less attention in clinical practice compared to cognitive impairments [49].…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic since low socioeconomic status is a well-known factor associated with several negative health outcomes (Ewart et al, 2017). Although the core symptoms of ADHD are a problem, living with ADHD may be a burden and affect self-image through feelings of powerlessness and a lack of social acceptance (Brod et al, 2012;Schrevel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%